Healthcare in the era of climate change and the need for environmental sustainability - Nicholas Chin Hock Tee; Jo-Anne Yeo; Mahesh Choolani; Kian Keong Poh; Tiing Leong Ang (Singapore Medical Journal)
Climate change is an existential threat to humanity. While the healthcare sector must manage the health-related consequences of climate change, it is a significant contributor to greenhouse gas emissions, responsible for up to 4.6% of global emission, aggravating global warming. Within the hospital environment, the three largest contributors to greenhouse gas emissions are the operating theatre, intensive care unit and gastrointestinal endoscopy. Knowledge of the health-related burden of climate change and the potential transformative health benefits of climate action is important to all health professionals, as they play crucial roles in effecting change. This article summarises the available literature on the impact of healthcare on climate change and efforts in mitigation, focusing on the intrinsic differences and similarities across the operating theatre complex, intensive care unit and gastrointestinal endoscopy unit. It also discusses strategies to reduce carbon footprint.